Bladesense – a novel approach for measuring dynamic helicopter rotor blade deformation - Weber, Simone; Southgate, Dominic; Mullaney, Kevin; James, Stephen W.; Rutherford, Robert; Sharma, Anuj; Lone, Mudassir; Kissinger, Thomas; Chehura, Edmond; Staines, Stephen; Pekmezci, Huseyin; Fragonara, Luca Zanotti; et al. (European Rotorcraft Forum, 2018)
Technologies that allow accurate measurement of rotorblade dynamics can impact almost all areas of the rotorcraft sector; ranging from maintenance all the way to blade design. The BladeSense project initiated in 2016 aims to take a step in developing and demonstrating such a capability using novel fibre optic sensors that allow direct shape measurement. In this article the authors summarise key project activities in modelling and simulation, instrumentation development and ground testing. The engineering approach and associated challenges and achievements in each of these disciplines are discussed albeit briefly. This ranges from the use of computational aerodynamics and structural modelling to predict blade dynamics to the development of direct fibre optic shape sensing that allows measurements above 1kHz over numerous positions on the blade. Moreover, the development of the prototype onboard system that overcomes the challenge of transferring data between the rotating main rotor to the fixed fuselage frames is also discussed.